The Impact of Monetary Policy on Bank Risk in the Western Balkan Countries - Gashi Fatmir; Fetai Besnik (SEEU Review, 2023)
The objective of this research paper is to examine the impact of monetary policy conditions on bank risk-taking in the Western Balkan countries. The paper tries to identify if monetary policy conditions, especially money interest rates, may induce a greater appetite for bank risk-taking in the Western Balkan countries. The impact of macroeconomic and banking indicators on bank risk-taking will be examined, too. For this purpose, we apply pooled OLS techniques, Fixed and Random effects panel, and Hausman-Taylor Instrumental IV model. The econometric results show a negative correlation between the monetary policy rate and bank risk-taking, rejecting the hypothesis that monetary policy rates indicate bank risk increase. However, expansive credit policies or loan portfolio growth have a positive impact on bank risk-taking in the Western Balkans. The study is original, and its findings will be of value to Central Banks and other policymakers in the Western Balkan countries.